2016
DOI: 10.1111/1440-1630.12333
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Orientation to daily Occupational Performance (COOP) as group therapy for children living with motor coordination difficulties: An integrated literature review

Abstract: The findings of this review suggest that the CO-OP approach, when administered in a group format, has the potential to benefit children living with motor coordination difficulties in both physical and psycho-social domains. More research is required to confirm these findings and contribute to evidence-based practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 44 publications
(142 reference statements)
0
10
0
Order By: Relevance
“…Our study adds to the growing body of evidence supporting occupational therapy interventions targeting transition to school and school-based occupations (Kadar et al, 2020; Anderson et al, 2017; Myers, 2008, Lust and Donica, 2011). Certainly, effect sizes were encouraging, particularly in light of the relative brevity of the program (Table 2).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Our study adds to the growing body of evidence supporting occupational therapy interventions targeting transition to school and school-based occupations (Kadar et al, 2020; Anderson et al, 2017; Myers, 2008, Lust and Donica, 2011). Certainly, effect sizes were encouraging, particularly in light of the relative brevity of the program (Table 2).…”
Section: Discussionmentioning
confidence: 78%
“…Group work is efficient in its utilisation of resources and has the potential for reducing waiting lists, possibility improving access to services. For some paediatric populations, groups are as effective as individual interventions for families’ satisfaction, improvement of children’s skills and overall cost-effectiveness (Camden et al, 2012; Anderson et al, 2017; Vertes et al, 2014).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…In some communities, a medical approach is seen as the dominant approach, however the efficacy of occupationbased interventions in children with CP has been reported in several studies. 36,37 Providing the parent with information about the type of intervention and how it can be effective in an understandable manner is important.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated the effectiveness of the original individual CO-OP-based training sessions for individual children with DCD (e.g., [ 5 ]) as well as variations of CO-OP group interventions ([ 7 ], for a review). Benefits of group interventions are the opportunity to meet other children and families facing similar difficulties and challenges and to learn from peers [ 8 ].…”
Section: Introductionmentioning
confidence: 99%